(untitled) (Singaporean Journal of Business Economics and Management, 2014)
This research has investigated the effect of meta- cognition skills on improving the instructional affairs in the view of high schools managers. The research method is descriptive- survey. The size of selected samples are 97 person (55 male and 42 female). The means of collecting data is a researcher- made question air in closed 25 closed answered questions about seven variables of research, analyzing duties, self- stimulation, self-controlling, self- observing, self- judgment, reaction to themselves and the different view of male and female managers about the effect of Meta cognition skills. For determining internal and external validity was used experts views. It was used Cronbach’s alpha coefficient for specifying the questionnaire reliability. It was used inferential and descriptive statistics for analyzing data. Findings show that meta- cognition skills recognition effect on improving instructional affairs. Analyzing duties, self- stimulation and self- controlling have respectively the most effect on improving instructional affairs. The effect of meta-cognition skills in the view of male and female managers is different.